A study of the user experience when interacting with applications that work with sports armbands to monitor human activity - Kiryczuk, Mateusz; Kocyła, Paweł; Dzieńkowski, Mariusz (Journal of Computer Sciences Institute, 2021)
This paper concerns the study of user experience and focuses on two aspects i.e. usability and user satisfaction. Two mobile applications for monitoring human activity, Mi Fit and Google Fit, were tested. Both applications work with sports armbands. Two methods were used for the study: a questionnaire and eye tracking. The comparison of the applications was made on the basis of the collected results from questionnaires, measurements of task completion times and the number and type of errors detected. Nine respondents participated in the study. The Google Fit application received a higher average score for user satisfaction, fewer errors and shorter task completion times.